2020
DOI: 10.3389/fnbeh.2020.576350
|View full text |Cite
|
Sign up to set email alerts
|

Navigation in a Space With Moving Objects: Rats Can Avoid Specific Locations Defined With Respect to a Moving Robot

Abstract: Animals can organize their behavior with respect to other moving animals or objects; when hunting or escaping a predator, when migrating in groups or during various social interactions. In rats, we aimed to characterize spatial behaviors relative to moving objects and to explore the cognitive mechanisms controlling these behaviors. Three groups of animals were trained to avoid a mild foot-shock delivered in one of three positions: either in front, on the left side, or on the right side of a moving robot. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…CA2 receives projections from the basal nucleus of the amygdala, which plays an important role for contextual fear conditioning (Pitkanen et al, 2000; Goosens & Maren, 2001). Ahuja et al (2020) demonstrated that CA1 pyramidal cells were responsive to a robot that indicates a shock zone. Robots have also been developed for the purpose of improving behavioral reproducibility when examining aspects of rodent spatial cognition in neuroscience.…”
Section: Introductionmentioning
confidence: 99%
“…CA2 receives projections from the basal nucleus of the amygdala, which plays an important role for contextual fear conditioning (Pitkanen et al, 2000; Goosens & Maren, 2001). Ahuja et al (2020) demonstrated that CA1 pyramidal cells were responsive to a robot that indicates a shock zone. Robots have also been developed for the purpose of improving behavioral reproducibility when examining aspects of rodent spatial cognition in neuroscience.…”
Section: Introductionmentioning
confidence: 99%
“…CA2 receives projections from the basal nucleus of the amygdala, which plays an important role for contextual fear conditioning ( Pitkänen et al, 2000 ; Goosens and Maren, 2001 ). Ahuja et al (2020) demonstrated that CA1 pyramidal cells were responsive to a robot that indicates a shock zone. Robots have also been developed for the purpose of improving behavioral reproducibility when examining aspects of rodent spatial cognition in neuroscience.…”
Section: Introductionmentioning
confidence: 99%
“…These RNN models [27,28], when trained on single agent path integration, have been shown to develop properties analogous to MEC. In particular, they exhibit units with grid, border, and spatially periodic "band" responses [27][28][29][30] and population dynamics consistent with continuous toroidal attractors [31,32]. While their biological plausibility remains unclear [33,34], we choose to analyze these RNN models for three reasons.…”
mentioning
confidence: 99%